High Incidence of Severe Combined Immunodeficiency Disease in Saudi Arabia Detected Through Combined T Cell Receptor Excision Circle and Next Generation Sequencing of Newborn Dried Blood Spots - Al-Mousa, Hamoud; Al-Dakheel, Ghadah; Jabr, Amal; Elbadaoui, Fahd; Abouelhoda, Mohamed; Baig, Mansoor; Monies, Dorota; Meyer, Brian; Hawwari, Abbas; Dasouki, Majed (Frontiers in Immunology, 2018)
Severe combined immunodeficiency disease (SCID) is the most severe form of primary immunodeficiency disorders (PID). T-cell receptor excision circle (TREC) copy number analysis is an efficient tool for population based newborn screening for SCID and other T cell lymphopenias. We sought to assess the incidence of SCID among Saudi newborn population and examine the feasibility of using targeted next generation sequencing PID gene panel (T-NGS PID) on DNA isolated from dried blood spots in routine newborn screening programs as a mutation screening tool for samples with low TREC count. Punches from 8718 Dried Blood Spots (DBS) collected on Guthrie cards were processed anonymously for the TREC assay. DNA was extracted from samples with confirmed low TREC count, then screened for 22q11.2 deletion syndrome by real time PCR and for mutations in PID related genes by T-NGS PID panel. Detected mutations were confirmed by Sanger sequencing. Sixteen out of the 8718 samples were confirmed to have low TREC copy number. Autosomal recessive mutations in AK2, JAK3 and MTHFD1 were confirmed in three samples. Two additional samples were positive for the 22q11.2 deletion syndrome. In this study, we provide evidence for high incidence of SCID among Saudi population (1/2906 live births) and demonstrate the feasibility of using T-NGS PID panel on DNA extracted from dried blood spots as a new reliable, rapid and cost-effective mutation screening method for newborns with low TREC assay, that can be implemented as part of newborn screening programs for SCID.